The nexus between Islamic banking and industrial production: empirical evidence from Malaysia - Khemaies Bougatef; Mohamed Sahbi Nakhli; Othman Mnari (ISRA International Journal of Islamic Finance, 2020)
Purpose: The purpose of this paper is to investigate the relationship between Islamic banking and industrial production by decomposing Islamic financing (IF) into profit and loss sharing (PLS) and non-profit and loss sharing (non-PLS) modes of financing. Design/methodology/approach This paper applies the autoregressive distributed lag (ARDL) approach and Toda and Yamamoto causality test on the monthly data set for Malaysia from 2010M1 to 2018M6. Findings The results reveal that IF plays an important role in boosting industrial production in the short run, as well as in the long run. Moreover, this positive effect mainly comes from non-PLS financing. In contrast, no significant relationship was found between PLS financing and industrial development neither in the short run nor in the long run. Practical implications The results have several policy implications. The existence of a time lag between the pooling of funds through PLS contracts and their channeling to industrial activities imply that Malaysian Islamic banks should maintain a long-term relationship with investment account holders. In addition, Islamic banks are called to increase the portion of PLS financing. The positive relationship between the industrial production index and IF (through non-PLS techniques) in the short and the long runs implies that policymakers in Malaysia should multiply their efforts to further expand the Islamic banking industry. Originality/value The originality of this study lies in decomposing Islamic banks' financing into PLS financing (muḍārabah and mushārakah) and non-PLS financing to assess the contribution of each mode of financing in industrial development.
Keywords: 330; Islamic banking; ARDL; Industrial production; PLS financing; Toda and Yamamoto causality test